Retropharyngeal abscess presenting as acute airway obstruction in a 66-year-old woman: A case report - Lin, Jian (World J Clin Cases, 2019)
BACKGROUND: Adult retropharyngeal abscess (RPA) is extremely rare, and most cases reported in the literature were related to tuberculous infection. We present a case of RPA with acute airway obstruction as the main manifestation in a 66-year-old woman that was considered to be non-tubercular suppurative inflammation in the retropharyngeal space. CASE SUMMARY: A 66-year-old woman complaining of chills and fever was admitted to our hospital. She was initially diagnosed with an acute upper respiratory tract infection. She lost consciousness twice during hospitalization. She regained consciousness immediately upon emergency tracheal intubation. Acute upper airway obstruction was suspected as arterial blood gas analysis showed obvious acute retention of carbon dioxide before the second tracheal intubation. The diagnosis of RPA was confirmed by computed tomography and magnetic resonance imaging. Kocuria kristinae was isolated from blood samples taken from both hands. The patient recovered and was subsequently discharged after receiving antibiotic therapy together with surgical incision and drainage of the abscess. CONCLUSION: Clinicians should be alert to the possibility of RPA in patients with acute airway obstruction. Surgical incision and drainage is an effective treatment for RPA.